VIOLATION OF BEHAVIOR STANDARDS IN A GENERAL SCHOOL: A HIDDEN FACTOR WEAKENING PSYCHOLOGICAL SAFETY IN THE PEDAGOGICAL COMMUNITY AND WAYS TO STABILIZE IT (Universal International Scientific Journal, 2026)
This article conceptualizes the violation of behavioral norms in the pedagogical team of a secondary school (such as interruptions, sarcasm, disdain, neglect, and withdrawal from discussion) as a hidden managerial factor that undermines psychological safety. When behavioral norms are violated, teachers' interpersonal risk behaviors such as asking questions, raising problems, admitting mistakes, and expressing opinions decrease; as a result, open communication and cooperation weaken, which can negatively affect the quality of decisions and the stability of implementation. The article explains this relationship through a chain of mechanisms and proposes organizational mechanisms such as standardizing behavioral standards within the framework of school management, introducing a constructive feedback procedure, strengthening transparent and explanatory decision-making practices, and establishing channels for raising problems.
Keywords: Standards of conduct, psychological safety, pedagogical team, open communication, leadership practices, managerial transparency, procedural fairness.